E-Governance and Grassroots Public Services in Local Government: A Study on The Taspen Smart Card Program For Pension Fund Services in Makassar City and Pinrang Regency - Lukman Nul Hakim Amran Saputra; Nur Khaerah; Abdillah Abdillah; Nuryanti Mustari (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to analyze the implementation of e-Government through Taspen Smart Card Program in pension fund services of State Civil Service. This study used a combination method of concurrent triangulation design (a balanced mix of quantitative and qualitative). The major instrument used was questionnaire and interview. There were participants of the Taspen Smart Card Program that involved as samples and informants in this study. The number of samples was 40 and 2 people as informants. The samples taken using probability sampling techniques. The data were analyzed using regression analysis technique. The results of this study indicated that the implementation of e- Government through Taspen Smart Card Program in pension fund services of State Civil Service in Pinrang and Makassar Regency is running very well. This is based on the average score obtained was 139.6 or 87.25% which indicates that the implementation of Taspen Smart Card fall into very good category. Furthermore, the study also shows that the implementation of Taspen Smart Card Program has a positive and significant effect in pension fund services of State Civil Service in Pinrang and Makassar Regency by 33.3% and the remaining 66.7% due to the existence of other programs issued by the government.